Personal Branding dan Pemimpin Kristen: Kepemimpinan dalam era Internet Of Things - Dwikoryanto, Matius I Totok; Arifianto, Yonatan Alex (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2023)
The main focus of this research is to explain how personal branding and Christian leaders: leadership in the internet of things era. The thing to remember is that the ambition to be famous is very easy to get in this era through social media, but the achievement to brand oneself must be in accordance with the norms and ethics that must be upheld. The research method used is in the form of descriptive qualitative research with a literature study approach. The purpose of this research is to provide input or ideas for Christian leaders so that they can promote themselves wisely and carefully in developing their leadership in the internet of things era. The conclusion of this research is that personal branding and Christian leaders as a leadership strategy in the era of the internet of things must be utilized as best as possible to reach out, serve, in pastoral care both online and face-to-face. So the first thing Christian leaders must understand is that the paradigm and nature of personal branding and its influence must be understood and actualized with the correct rules and norms. Christian leaders also know the boundaries and scope of Christian leadership. And of course Christian leaders can see opportunities for promotion of their leadership in accordance with humility as the basis for receiving God's grace and plans, of course, according to God's will and plan. So that Christian leaders can actualize Christian leadership in the internet of things era as a form of reaching out and serving those who are in an internet of things connection.AbstrakFokus utama penelitian ini adalah menjelaskan bagaimana personal branding dan pemimpin Kristen: kepemimpinan dalam era internet of things. Hal yang perlu diingat dalam kepemimpinan saat ini bahwa ambisi untuk terkenal tersebut didapat dengan sangat mudah di era digital saat ini melalui media sosial, namun pencapaian untuk membranding dirinya haruslah sesuai dengan norma dan etika yang harus dijunjung. Adapun metode penelitian yang digunakan yaitu berupa penelitian kualitatif deskritif dengan pendekatan studi literature. Tujuan penelitian ini yaitu untuk memberikan masukan ide atau gagasan bagi para pemimpin Kristen supaya mereka  bijaksana dan penuh kehati-hatian dalam mempromosikan dirinya dengan benar di dalam pengembangan kepemimpinannya di era internet of things. Kesimpulan dari penelitian ini adalah personal branding dan pemimpin Kristen sebagai strategi kepemimpinan dalam era internet of things harus dapat dimanfaatkan sebaik mungkin untuk menjangkau, melayani, dalam pelayanan pastoral baik secara online maupun dalam keseharian tatap muka kepada khalayak ramai. Maka yang pertama para pemimpin Kristen haruslah mengerti bahwa paradigma dan hakikat personal branding dan pengaruhnya harus dimengerti dan diaktualisasikan dengan kaidah dan norma yang benar. Pemimpin Kristen juga mengetahi batasan dan ruang lingkup kepemimpinan Kristen. Dan tentunya pemimpin Kristen dapat melihat peluang promosi kepemimpinannya sesuai dengan kerendahan hati sebagai dasar untuk mendapat kasih karunia Allah dan tentunya sesuai dengan kehendak dan rencana Tuhan. Sehingga pemimpin Kristen dapat mengaktulisasi kepemimpinan Kristen di era internet of things sebagai bentuk untuk menjangkau dan melayani mereka yang berada dalam koneksi internet of things.